2014
DOI: 10.1097/wnn.0000000000000026
|View full text |Cite
|
Sign up to set email alerts
|

A Girl with Tuberous Sclerosis Complex Presenting with Severe Epilepsy and Electrical Status Epilepticus During Sleep, and with High-Functioning Autism and Mutism

Abstract: Most patients with tuberous sclerosis complex (TSC) suffer from epilepsy, and many have cognitive and behavioral problems like severe intellectual disability, autism, and hyperactivity. Only rare patients with TSC and autism have a normal intelligence quotient. We report a 13-year-old girl with definite TSC who had early-onset severe epilepsy, autistic behavior, and moderate developmental delay. By school age, however, she had normal intelligence; her intelligence quotient was at least 70 based on a Stanford-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…TSC2, the previously reported causal gene DEPDC5, as well as the de novo mutated NPRL3 gene in this study are all mTOR-signalling regulatory genes that are highly associated with malformations of cortical development [22,23]. Pacheva et al [24] reported the case of a 13-year-old girl with tuberous sclerosis complex, who presented with severe epilepsy, autism and ESES on EEG. Coincidentally, in the recently published study of Rudolf et al [18], a de novo variant of TSC2 was also found in a patient with ARE, moreover, the authors also identified ADGRV1 variants, which were found in two patients in this study.…”
Section: Discussionsupporting
confidence: 54%
“…TSC2, the previously reported causal gene DEPDC5, as well as the de novo mutated NPRL3 gene in this study are all mTOR-signalling regulatory genes that are highly associated with malformations of cortical development [22,23]. Pacheva et al [24] reported the case of a 13-year-old girl with tuberous sclerosis complex, who presented with severe epilepsy, autism and ESES on EEG. Coincidentally, in the recently published study of Rudolf et al [18], a de novo variant of TSC2 was also found in a patient with ARE, moreover, the authors also identified ADGRV1 variants, which were found in two patients in this study.…”
Section: Discussionsupporting
confidence: 54%
“…Interestingly, ESES, has been recently reported in one individual with WAC-related ID, however, the details of his phenotype are partially available for comparison [9]. A status epilepticus during sleep has been observed in other syndromes such as Rett syndrome, Christianson syndrome, and other autism spectrum disorders [38][39][40]. Clinical consequences of ESES in neurodevelopmental disorders, especially those characterized by regression, or in neurodegenerative disorders [38], are much more difficult to assess.…”
Section: Wac Phenotype Heterogeneitymentioning
confidence: 99%
“…It has long-term poor prognosis due to the persistence of neuropsychological impairment. Despite the fact that the ESESS/CSWSS pattern can be seen in ESESS/CSWSS/epilepsy-aphasia spectrum, it can also concur with other syndromes such as Rett syndrome, Costeff syndrome, Christianson syndrome, Tuberous sclerosis complex, Cohen syndrome and autism spectrum disorders [ 10 15 ].…”
Section: Introductionmentioning
confidence: 99%